2019
DOI: 10.1213/ane.0000000000004585
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events During Intrahospital Transport of Critically Ill Children: A Systematic Review

Abstract: Intrahospital transport of a critically ill patient is often required to achieve a diagnostic and/or therapeutic objective. However, clinicians who recommend a procedure that requires transport are often not fully aware of the risks of transport. Clinicians involved in the care of critically ill children may therefore benefit from a clear enumeration of adverse events that have occurred during transport, risk factors for those events, and guidance for event prevention. The objective of this review was to colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
0
25
1
2
Order By: Relevance
“…Yet, the rate of complicated transports (25%) is at the low end of previous reports (25-80%) in adults, children, and newborns (1-7, 11, 24-26). In contrast to studies performed in children and adults, we did not observe any transport-related life-threatening or fatal adverse events such as cardiac arrest or unplanned extubation (9,11). AEs were mainly related to instability of the cardiovascular and respiratory systems, agitation, and temperature control.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Yet, the rate of complicated transports (25%) is at the low end of previous reports (25-80%) in adults, children, and newborns (1-7, 11, 24-26). In contrast to studies performed in children and adults, we did not observe any transport-related life-threatening or fatal adverse events such as cardiac arrest or unplanned extubation (9,11). AEs were mainly related to instability of the cardiovascular and respiratory systems, agitation, and temperature control.…”
Section: Discussioncontrasting
confidence: 99%
“…Critically ill adult and pediatric patients transported during mechanical ventilation or hemodynamic support are at the greatest risk of AEs (1,3,5,9). We found that hemodynamic support with catecholamines or prostaglandins, and the presence of a central venous catheter were strongly associated with AEs.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Still, concerns for a Hawthorne effect limiting the internal validity of the checklist disallowed such a design. 33 …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review specifically addresses adverse events during intrahospital transport of critically ill children. 31 This review included 24 studies with a total of 4,104 transports. In this group of pediatric subjects, respiratory and airway events were the most common adverse events, and the risk of an adverse event increased as the severity of underlying illness and the degree of respiratory support increased.…”
Section: Adverse Events During Intrahospital Transportmentioning
confidence: 99%